12 Diagnostic and prognostic utility of cardiovascular magnetic resonance imaging in heart failure with preserved ejection fraction. (18th April 2016) - Kanagala, P; Cheng, ASH; McAdam, J; Marsh, AM; Squire, IB; Ng, LL; McCann, GP
Abstract : Purpose: Heart failure with preserved ejection fraction (HFpEF) is a poorly characterised condition. We aimed to phenotype patients with HFpEF using multiparametric stress cardiovascular magnetic resonance imaging (CMR) and assess the relationship to clinical outcomes. Methods and Results: Patients were recruited as part of an observational, single-centre, cohort study. Inclusion criteria were: clinical or radiographic evidence of heart failure (HF) and ejection fraction > 50% on transthoracic echocardiography (TTE). Exclusion criteria were: myocardial infarction (MI) in the preceding 6 months, suspected or confirmed cardiomyopathy/ constrictive pericarditis, non-cardiovascular life expectancy < 6 months and severe valve/ lung/ renal disease. Patients labelled as HFpEF (n = 154, 51% male, mean age 72.4 ± 10 years) underwent TTE and CMR during a single study visit. The CMR protocol comprised cine, stress/rest perfusion and late gadolinium enhancement imaging on a 3-Tesla scanner. Follow-up outcome data (death or HF hospitalisation) was captured after a minimum of 6 months. CMR detected previously undiagnosed pathology in 42 patients (27%), who had similar baseline characteristics to those without a new diagnosis (see Table 1 ). These diagnoses consisted of: coronary artery disease (n = 20, including 14 with 'silent' MI), microvascular dysfunction (n = 11), probable or definite hypertrophic cardiomyopathy (n = 10) and constrictive pericarditis (n = 5). Four patients had dual pathology. During follow-up (median = 623 days), those patients with a new CMR diagnosis were at higher risk (see Figure 1 ) of adverse outcome for the composite end-point (hazard ratio log rank test: p = 0.047). In multivariate analysis, the 'new CMR diagnoses' group remained an independent predictor of outcome (hazard ratio: 1.92; 95% CI: 1.07 to 3.45; p = 0.03). Conclusion: Stress CMR diagnosed new significant pathology in 27% of patients with HFpEF and these patients were at increased risk of death and HF hospitalisation. Conflicts of interest: On behalf of all authors, there are no conflicts of interest to declare.